Response of Rainfed Castor to Soil and Foliar Application of Zinc and Iron Micronutrients - Ramanjaneyulu, A. V.; Madhavi, A.; Kumar, M. V. Nagesh; Neelima, T. L. (International Journal of Bio-resource and Stress Management, 2021)
A field investigation was carried out to study the influence of zinc and iron micronutrients on the performance of rainfed castor, in Professor Jayashankar Telangana State Agricultural University, Telangana state, India for three consecutive years during kharif 2011-12, 2012-13 and 2013-14. There were nine treatments viz., Control (no micronutrient application); soil application of FeSO4 @ 15 kg ha-1; soil application of FeSO4 @ 25 kg ha-1; soil application of ZnSO4 @ 15 kg ha-1; soil application of ZnSO4 @ 25 kg ha-1; foliar application of 0.5% FeSO4 at 50 DAS; foliar application of 0.5% FeSO4 at 50 and 90 DAS; foliar application of 0.5% ZnSO4 at 50 DAS; foliar application of 0.5% ZnSO4 at 50 and 90 DAS and tested in randomized block design with three replications. The foliar application of ZnSO4 (0.5%) twice at 50 and 90 DAS resulted in significantly higher seed yield (1698 kg ha-1), higher gross returns (Rs. 54344 ha-1), net returns (Rs. 33501 ha-1) and B:C ratio (2.60) over rest of the treatments. The seed yield improvement was to the tune of 54% over no micronutrient application. The uptake of major and micronutrients was greater when the crop received two sprays of ZnSO4 as compared toone spray of ZnSO4, two sprays of FeSO4 and soil application of either of the micronutrients. The castor bean crop responded to Zn better than Fe by producing 10.2% to 12.2% higher seed yield. Foliar spray was found superior to soil application in case of both the micronutrients.